Coherence and Cohesion Shifts in the Students’ Translated Text - Resty Wahyuni; Busmin Gurning; T. Sylvana Sinar (Universitas Negeri Medan, 2015)
The aims of this study are to describe : 1) the types of translation procedures used in the translated text done by the students, 2 ) the types of cohesion shifts used in the translated text done by the students, 2) the types of coherence shifts used in the translated text done by the students. The data were taken from the translated text of students of English faculty at Alwasliyah University of North Sumatra. They were analyzed by using some steps. First, the researcher selected translated text which contain cohesion and coherence shifts. Second, the translated text were classified based on Blum – Kulka’s theory. Having analyzed the data from translated text of students which consists of six paragraphs, the findings are presented as follows : 1). There are five translation procedures which are applied by the students in translating text. They are modulation (29), reduction (8), deletion (2), naturalization (5) and reduction+modulation (2), 2). There are 39 cohesion shifts which are used by the students namely 37 cohesion shifts in text meaning and 2 cohesion shifts in level of explicitness, 3). there are 38 coherence shifts which were used by the students namely 32 reader-focused shifts of coherence and 6 text-focused shifts of coherence. Keywords: Coherence; cohesion; coherence shifts; cohesion shifts; and translation.